ORGANIZATIONAL CULTURE AND ORGANIZATIONAL COMMITMENT TO ORGANIZATIONAL CITIZENSHIP BEHAVIOR - Rini Rahmawati; Muhammad Rowi Ashari; Asrid Juniar; Ashari Sofyaun (ITB AAS Indonesia Surakarta, 2023)
Abstract This study aims to analyze the effect of Organizational Culture and Organizational Commitment on Organizational Citizenship Behavior (OCB) conducted on Hasnur Polytechnic Employees. The population in this study were 61 employees of the Hasnur Polytechnic. The sampling technique used is nonprobability sampling with the technique used is census or total sampling so that the sample used is the entire population of 61 people. This type of research is quantitative by using a questionnaire in data collection. Data analysis technique using Multiple Linear Regression Analysis. The results of this study indicate that Organizational Culture and Organizational Commitment have a positive and significant effect on Organizational Citizenship Behavior (OCB). Employees who have a strong organizational culture supported by good organizational commitment will be able to create OCB, namely doing work outside their job description according to the job description without having to be forced or do it voluntarily. The results of this study are expected to be input for organizations to pay attention to organizational culture and organizational commitment to produce Organizational Citizenship Behavior (OCB). Keywords : Organizational Culture, Organizational Commitment, OCB